Semântica da Libras: hiperônimos e hipônimos e o desenvolvimento linguístico da criança surda - Santos, Marcos de Moraes (2018)
Do deaf kids, when they need to specify animals such as dogs and cats, use more hyponyms or hyperonyms? The present study has the goal of investigating how the hyperonymic and hyponymic relations are stablished in Libras aiming at identifying the strategies used by the kids to identify the animals. To accomplish this research we used the theoretical contributions through the innatist theory (CHOMSKY, 1959, 1977, 1981, 1994) and through the studies of semantics and lexicon, from the reflections brought by Lyons (1977), Johnston and Schembri (2007) and Vidal (2011). Methodologically, we made an experimental research with production tasks elicited (GROLLA; SILVA, 2014) in which figures with different species of the animals CAT, BIRD, MONKEY and CAT were presented to the deaf and listener children so they could identify the animals. Following that, we identified the types of identification produced by the listener and deaf groups of kids and made a descriptive and statistical analysis of the data. The results pointed out that deaf and listener children made more hyperonyms than hyponyms and this difference was statistically relevant. Among the types of hyperonyms, to the deaf group the composition strategies of the hyperonym with a modificator were highlighted, this being a sign of the native lexicon or a representation sign. To the listener group the standard lexical items were highlighted. In the relation between the deaf and listener groups, there was no relevant statistic difference, existing a slight startle of the hyperonyms to the listener children. In other words, deaf and listener kids produce more hyperonyms than hyponyms when they need to identify the referred animals and that there is no difference between deaf and listeners according to the proportion in the production of hyperonyms and hyponyms, the difference is only in the types of strategy. We concluded, therefore, that the production of hyponyms or not is not a problem in Libras, because the Libras lexicon is capable of organizing and generating relations between their items so that the users may be able to express themselves. It is made necessary; however, that the deaf children have more access to knowledge in their mother language and that the apprenticeship would not be only available in the school environment. The lexical acquisition of the deaf child will depend on the effective contact with Libras and the extension of this lexicon is related to the Libras contact in diverse conceptual fields.